Water-based mildew-proof, moisture-proof, sound-insulating, sound-absorbing and high environmental protection elastic wall coating and preparation method thereof

CN122978798APending Publication Date: 2026-10-27SUZHOU HIGH-TECH DACHENG LOW-CARBON ENVIRONMENTAL PROTECTION NEW MATERIAL DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610973993.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-01
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]然而,上述墙体涂料在实际应用中普遍存在功能单一、综合性能不足的问题

Benefits of technology

1、本申请通过采用以有机硅/丙烯酸酯共聚物为核、含氟/丙烯酸酯共聚物为壳的核壳结构改性丙烯酸酯乳液,使含氟疏水链段富集于涂层表面、有机硅弹性链段集中于涂层内部,实现了涂层内部的界面功能分区,在不添加传统有害防霉剂的前提下获得了长效防霉防潮性能,同时赋予涂膜优异的弹性抗开裂能力,显著提升了涂料的环保性和耐久性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to a water-based mildew-proof and moisture-proof sound insulation and sound absorption high-environmental-protection elastic wall coating and a preparation method thereof. The preparation raw materials comprise the following components in parts by weight: modified acrylate emulsion 40-60 parts, pigment and filler 20-30 parts, fumed silica 1-10 parts, glass fiber 5-15 parts, additive 1-10 parts, water 1-10 parts and thickening agent 0.1-1%. The modified acrylate emulsion is a core-shell structure emulsion with organic silicon monomer / acrylate copolymer as the core and fluorine-containing monomer / acrylate copolymer as the shell. The hydrophobic moisture-proof effect of the fluorine-containing shell layer in the core-shell structure emulsion, the high elasticity of the organic silicon core layer and the synergistic cooperation between the multilayer sound insulation and sound absorption structure formed by the fumed silica and the glass fiber enable the coating to unexpectedly have the comprehensive performance of high elasticity and anti-cracking, long-term mildew-proof and moisture-proof, high-efficiency sound insulation and sound absorption and high environmental protection under low construction thickness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of architectural coatings, and in particular to a water-based, mildew-proof, moisture-proof, sound-absorbing, environmentally friendly, and elastic wall coating and its preparation method. Background Technology

[0002] Wall coatings are widely used for the decoration and protection of interior and exterior walls of buildings. Common wall coatings on the market include ordinary latex paint, elastic coatings, anti-mildew coatings, and sound-insulating coatings. Ordinary latex paint offers good decorative properties and is washable; elastic coatings improve the crack resistance of the coating film by introducing elastic resins; anti-mildew coatings add bactericidal and anti-mildew components to inhibit mold growth; and sound-insulating coatings typically use thick-layer mortar or fiber-reinforced systems to reduce noise transmission.

[0003] However, the aforementioned wall coatings generally suffer from limited functionality and insufficient overall performance in practical applications. Specifically: ordinary latex paint films are brittle and prone to cracking when the substrate deforms or temperature changes, and they lack sound insulation; elastic coatings have dense films with poor breathability, making them susceptible to blistering, peeling, or mold growth in humid environments, resulting in poor moisture and mildew resistance; traditional mildew-resistant coatings often add formaldehyde-releasing preservatives or heavy metal compounds to achieve bactericidal effects, posing potential hazards to human health and the environment; existing sound-insulating coatings are mostly cement-based or thick mortar systems, requiring large application thicknesses, resulting in rough surfaces and poor decorative properties, making them unsuitable for direct use as a finishing layer. In summary, existing technologies cannot simultaneously meet the multiple requirements of crack resistance, mildew prevention, moisture resistance, sound insulation, environmental protection, and decorative properties.

[0004] Therefore, there is still a need in this field to develop a wall coating that can comprehensively solve the above-mentioned defects, that is, a wall coating product that simultaneously has good crack resistance, mildew and moisture resistance, sound insulation and sound absorption, high environmental protection and good decorative effect, and has a moderate construction thickness and can be used directly as a finishing layer. Summary of the Invention

[0005] In order to comprehensively improve the crack resistance, mildew and moisture resistance, sound insulation and sound absorption and environmental protection performance of wall coatings, this application provides a water-based mildew and moisture resistance, sound insulation and sound absorption, highly environmentally friendly and elastic wall coating and its preparation method.

[0006] In the first aspect, this application provides a water-based, mildew-proof, moisture-proof, sound-insulating, sound-absorbing, highly environmentally friendly, and elastic wall coating, employing the following technical solution: A water-based, mildew-proof, moisture-proof, sound-absorbing, environmentally friendly, and elastic wall coating is prepared by means of the following components by weight: 40-60 parts of modified acrylic emulsion, 20-30 parts of pigments and fillers, 1-10 parts of fumed silica, 5-15 parts of glass fiber, 1-10 parts of additives, 1-10 parts of water, and 0.1-1% of thickener; the modified acrylic emulsion is a core-shell emulsion with an organosilicon monomer / acrylate copolymer as the core and a fluorinated monomer / acrylate copolymer as the shell.

[0007] The inventors discovered that by using a core-shell structure modified acrylic emulsion, hydrophobic fluorinated segments are enriched in the shell layer and elastic organosilicon segments are concentrated in the core layer, achieving functional zoning of the interface within the coating. Combined with a multilayer reflective-scattering-absorption acoustic structure formed by fumed silica and glass fiber, it was unexpectedly found that excellent elastic crack resistance, long-lasting mildew and moisture resistance, high-efficiency sound insulation and absorption, and high environmental friendliness can be obtained simultaneously with a coating thickness of 3-5mm.

[0008] Specifically, after the wall paint has cured, the surface moisture retention time is significantly shortened due to the hydrophobic effect of the fluorinated shell in the emulsion, thus effectively inhibiting the adhesion and reproduction of mold. Even if there are local defects on the coating surface, the dense film provided by the core-shell structure can prevent moisture from penetrating to the substrate, eliminating mold growth at its source. This mechanism avoids the use of traditional anti-mold agents and significantly improves the environmental performance of the paint.

[0009] The high elasticity provided by the core layer of organosilicon in the emulsion, combined with the high modulus of glass fiber and the nano-reinforcing effect of fumed silica, allows the coating to maintain excellent elongation at break while also unexpectedly improving tensile strength, achieving a mechanical balance of "both soft and strong" and overcoming the defect of ordinary elastic coatings that "becomes softer the more elastic they become".

[0010] Glass fibers form a three-dimensional interwoven fiber skeleton in the coating: on the one hand, they act as a reinforcement, significantly improving the tensile strength and crack resistance of the coating; on the other hand, micron-nano level interfaces are formed between fibers and between fibers and nanoparticles. When sound waves reach these interfaces, they are strongly reflected and scattered due to impedance mismatch, prolonging the sound wave propagation path, thus achieving significant sound insulation improvement even with a thin coating thickness of 3-5 mm.

[0011] Meanwhile, the thixotropic properties of fumed silica ensure good leveling and prevent sagging during coating application. After being uniformly dispersed in the coating, it forms a loose, nanoporous network. When sound waves enter the coating, they undergo multiple reflections, refractions, and viscous losses within the nanopores, converting sound energy into heat energy and being absorbed, thus giving the coating a high sound absorption coefficient. Furthermore, the abundant silanol groups on the surface of the nanoparticles can form hydrogen bonds or chemical bonds with the emulsion film-forming material, enhancing the coating's cohesive strength. The nanoporous sound absorption of fumed silica and the reflective and scattering sound insulation of glass fibers complement each other, forming a multi-layered acoustic structure of "absorption-reflection-absorption," comprehensively improving the coating's noise reduction capabilities.

[0012] In summary, this application, through the interfacial functional zoning design of the core-shell structure emulsion and its coupling with the multi-level acoustic structure constructed of fumed silica / glass fiber, unexpectedly achieves high elasticity and crack resistance, long-lasting mildew and moisture resistance, high efficiency sound insulation and absorption, and high environmental friendliness simultaneously, without the need for harmful additives and with a thickness of only 3-5mm.

[0013] In one specific implementation, the preparation of the modified acrylate emulsion includes the following steps: S1. After mixing water, emulsifier, and sodium bicarbonate, add a mixture of core layer monomers (including n-butyl acrylate, methyl methacrylate, and organosilicon monomers) dropwise. After stirring and pre-emulsifying, add ammonium persulfate initiator solution dropwise to react and form a core layer seed emulsion. S2. Mix water, emulsifier and shell monomer mixture (including n-butyl acrylate, dodecafluoroheptyl methacrylate and functional monomers) to form shell pre-emulsion; S3. The shell pre-emulsion obtained in step S2 is added dropwise to the core seed emulsion obtained in step S1 to carry out a core-shell polymerization reaction. Ammonium persulfate initiator solution is added to carry out a ripening reaction. The modified acrylate emulsion is then obtained through post-treatment.

[0014] Preferably, the functional monomer in step S2 is selected from one or two of glycidyl methacrylate and hydroxyethyl acrylate; more preferably, the functional monomer is glycidyl methacrylate.

[0015] The modified acrylic emulsion prepared by the above steps has a core-shell structure with an organosilicon / acrylate copolymer as the core and a fluorinated / acrylate copolymer as the shell. The fluorinated segments in the shell layer endow the coating with excellent hydrophobic and moisture-proof properties and low surface energy characteristics, while the organosilicon segments in the core layer endow the coating with good flexibility and crack resistance. The epoxy groups provided by glycidyl methacrylate as a functional monomer can participate in subsequent crosslinking reactions, further enhancing the cohesion and water resistance of the coating film. This lays the foundation for wall coatings to achieve long-lasting mildew prevention, high elasticity, sound insulation and absorption, and high environmental protection.

[0016] In one specific implementation, in the preparation of the modified acrylate emulsion described above, the weight ratio of the core monomer mixture to the shell monomer mixture is (0.8-1.2):1.

[0017] Through extensive experimentation, the inventors verified that when the weight ratio of the core layer monomer mixture to the shell layer monomer mixture is controlled within the range of (0.8-1.2):1, the resulting modified acrylate emulsion achieves an optimal balance between elasticity and hydrophobic moisture-proof properties in the coating film. At this ratio, the silicone elastic segments provided by the core layer and the fluorinated hydrophobic segments provided by the shell layer form a continuous, dense, and firmly bonded core-shell structure in the coating film. This ensures sufficient flexibility and crack resistance during substrate deformation while also imparting excellent hydrophobicity to the coating surface. Simultaneously, the crosslinking sites provided by the functional monomers in the shell layer further enhance the cohesive strength and water resistance of the coating film, laying a solid foundation for the subsequent compounding with fillers such as fumed silica and glass fiber to prepare high-performance wall coatings.

[0018] When the proportion of core layer monomers is too high, the shell layer monomers are relatively insufficient, which leads to the shell layer monomers not being able to completely coat the core layer seed emulsion. Some core layer polymers are exposed on the surface of latex particles, making it impossible for fluorinated segments to be effectively enriched on the coating surface. This significantly reduces the hydrophobic and moisture-proof properties, decreases the water contact angle, and weakens the anti-mildew effect. Furthermore, excessive organosilicon segments make the coating overly soft. Although the elongation at break is further improved, the tensile strength is significantly reduced. The coating is prone to plastic deformation or creep when subjected to external forces, and its scratch resistance and abrasion resistance deteriorate, resulting in the defect of "becoming softer the more elastic it is." Modified acrylic emulsions also suffer from weakened interfacial bonding between latex particles with insufficient fluorinated segments and fillers such as fumed silica and glass fiber due to the lack of sufficient fluorinated segments on the surface. This leads to poor filler dispersion uniformity, affecting the formation of sound insulation and sound absorption structures, and ultimately reducing the sound insulation effect.

[0019] When the proportion of shell monomers is too high, the core monomers are relatively insufficient, resulting in high rigidity of fluorinated segments. Excessive introduction will cause the overall stiffness of the coating film to be too high, the flexibility to decrease, and the elongation at break to decrease simultaneously. When the wall substrate undergoes thermal expansion and contraction or slight deformation, the coating is prone to cracking, powdering, or peeling, losing the crack resistance advantage of elastic coatings. The compatibility between fluorinated polymers and acrylate polymers is limited. When the shell layer is too thick, the internal stress of the latex particles increases, and phase separation may occur during film formation, resulting in a rough coating appearance, reduced gloss, and even microcracks or pinhole defects. Furthermore, the price of fluorinated monomers (such as dodecafluoroheptyl methacrylate) is much higher than that of ordinary acrylate monomers. An excessively high proportion of shell monomers will significantly increase the raw material cost and reduce the market competitiveness of the product. In addition, excessive accumulation of fluorinated segments on the coating surface, although enhancing hydrophobicity, may also reduce the adhesion between the coating and hydrophilic wall substrates (such as cement mortar and putty layers), leading to blistering and peeling of the coating after long-term use.

[0020] In one specific implementation, the fumed silica is modified with a silane coupling agent; more preferably, the silane coupling agent is KH-570.

[0021] By modifying fumed silica with KH-570, the alkoxy groups in KH-570 hydrolyze to form silanols, which then undergo a condensation reaction with the silanols on the surface of fumed silica to form covalent bonds. This anchors the carbon-carbon double bonds in KH-570, which can participate in free radical polymerization, onto the surface of the fumed silica. When the modified fumed silica is mixed with a modified acrylate emulsion, the double bonds on its surface can crosslink with the acrylate copolymer in the emulsion, thus firmly anchoring the inorganic nanoparticles to the polymer network through covalent bonds. This significantly improves the dispersion stability of fumed silica in the coating system, preventing the agglomeration of nanoparticles. Furthermore, it enhances the interfacial bonding strength between the inorganic filler and the organic film-forming material, allowing the nanoporous structure of fumed silica to more effectively synergistically construct a stable "absorption-reflection-absorption" multilayer acoustic structure with glass fibers, further improving the sound insulation and absorption performance, mechanical strength, and durability of the coating.

[0022] Meanwhile, the organic segments on the surface of the fumed silica modified by KH-570 also endow it with a certain degree of hydrophobicity, which complements the hydrophobic effect of the fluorine-containing shell, synergistically reducing the water absorption rate of the coating and enhancing the long-lasting anti-mildew and moisture-proof effect.

[0023] In one specific implementation, the pigment and filler are selected from one or two of titanium dioxide and talc; more preferably, the pigment and filler include titanium dioxide and talc, and the weight ratio of titanium dioxide to talc is (2-5):1.

[0024] The inventors discovered that when the weight ratio of titanium dioxide to talc is controlled within the range of (2-5):1, the resulting wall coating achieves an optimal balance between hiding power, scrub resistance, gloss, and mechanical properties. Titanium dioxide (such as rutile titanium dioxide) has a high refractive index and excellent light scattering ability, serving as the main white pigment and hiding power source in this coating system. Its high reflectivity also helps reduce the surface temperature of the coating, indirectly inhibiting mold growth. Talc (such as silicate minerals) has a flake-like structure that fills the gaps between titanium dioxide particles, improving the density and gloss of the coating film and significantly enhancing its abrasion resistance and sandability. When the two are blended at a ratio of (2-5):1, titanium dioxide provides sufficient hiding power, while talc improves the application feel and coating smoothness. Simultaneously, the flake-like talc forms a multi-scale reinforcing network with glass fiber and fumed silica, further synergistically enhancing the coating's crack resistance and sound insulation properties.

[0025] When the proportion of titanium dioxide is too high, resulting in insufficient talc, the gaps between titanium dioxide particles cannot be effectively filled. This increases the porosity of the coating, reducing its density and allowing moisture and harmful substances to penetrate more easily, thus weakening its moisture-proof and mildew-proof effects. Furthermore, because the flaky structure of talc has lubricating and reinforcing properties, a lack of sufficient talc will increase the surface friction coefficient of the coating, potentially reducing the number of scrub cycles and affecting its lifespan. Simultaneously, an excessively high proportion of titanium dioxide may increase the surface roughness of the coating, exacerbate light scattering, and decrease or unbalance the gloss, affecting the decorative effect of the wall. Moreover, titanium dioxide is much more expensive than talc, and an excessively high proportion of titanium dioxide will significantly increase raw material costs and reduce economic efficiency.

[0026] When the proportion of talc is too high, because the refractive index of talc is much lower than that of titanium dioxide, the hiding power of talc per unit mass is far less than that of titanium dioxide. The coating cannot effectively cover the base color of the substrate, and more coats must be applied to achieve a satisfactory hiding effect. Excessive talc will also destroy the continuous phase of polymer film formation, making the coating brittle, reducing its flexibility, significantly decreasing its elongation at break, and weakening its crack resistance. At the same time, the coating surface is prone to chalking, and its scrub resistance is also significantly reduced. Furthermore, because talc is flaky and hydrophobic, excessive addition will interfere with the dispersion of glass fibers in the coating, thereby weakening the reinforcing effect of the fiber skeleton and reducing the sound insulation and absorption performance. In addition, when there is insufficient titanium dioxide, the coating surface's ability to shield against ultraviolet rays decreases. Therefore, the coating may undergo photodegradation or yellowing and discoloration when exposed to sunlight for a long time.

[0027] In one specific implementation, the additives include dispersants, wetting agents, defoamers, film-forming aids, preservatives, and pH adjusters.

[0028] By adopting the above technical solution, this application takes into account both performance requirements and environmental protection requirements in the selection of additives. Specifically: dispersants, wetting agents, defoamers, and pH adjusters are essential for the coating system, and are used to ensure the uniform dispersion of pigments and fillers, sufficient wetting of the substrate, elimination of bubbles during production and construction, and pH stability of the system, respectively; film-forming aids are selected from low-VOC varieties to promote the fusion and film formation of latex particles at ambient temperature, while minimizing their dosage; since necessary in-tank protection has already been introduced during the emulsion polymerization stage, preservatives are only added in very small amounts when formulating the coating, and environmentally friendly products free of formaldehyde and isothiazolinone-like sensitive components are preferred.

[0029] Most importantly, this application does not add any traditional antifungal agents (such as o-phenylphenol, BIT20, etc.). The long-lasting antifungal and moisture-proof performance of the coating relies entirely on the hydrophobic effect and dense film-forming characteristics of the fluorinated shell in the core-shell structure emulsion, thereby avoiding the potential harm of toxic bactericides to human health and the environment from the source, and truly achieving the high environmental protection goal of "simplified additives and excellent performance".

[0030] Secondly, this application provides a method for preparing a water-based, mildew-proof, moisture-proof, sound-insulating, sound-absorbing, highly environmentally friendly, and elastic wall coating, using the following technical solution: A method for preparing a water-based, mildew-proof, moisture-proof, sound-insulating, sound-absorbing, environmentally friendly, and elastic wall coating includes the following steps: The additives are dispersed in water and stirred evenly. Under stirring conditions, pigments, fillers, fumed silica, and glass fiber are added in sequence, followed by modified acrylic emulsion. The mixture is stirred evenly, and finally, a thickener is added to adjust the viscosity of the coating to 80-120 KU. The coating is then filtered to obtain the water-based anti-mildew, moisture-proof, sound-insulating, sound-absorbing, environmentally friendly, and elastic wall coating.

[0031] The water-based anti-mildew, moisture-proof, sound-absorbing, environmentally friendly, and elastic wall coating prepared by the above steps has uniform distribution of its components and a stable system. After curing, it can form a multi-layer composite structure with core-shell emulsion as the connecting phase, glass fiber as the skeleton, and fumed silica filling the pores, thus stably endowing the coating with comprehensive performance of high elasticity, crack resistance, long-lasting anti-mildew and moisture-proof, high-efficiency sound insulation and absorption, and high environmental protection.

[0032] During the preparation process, the pre-dispersed aqueous phase of the additives ensures that the previously added pigments, fillers, fumed silica, and glass fibers are fully wetted and uniformly dispersed, avoiding potential agglomeration or flocculation when these fillers are directly mixed with the high-concentration emulsion. Simultaneously, the addition of the modified acrylic emulsion in a subsequent stage effectively protects the integrity of the core-shell structure, thereby ensuring the coating's storage stability, application leveling properties, and anti-sagging properties.

[0033] In summary, this application includes at least one of the following beneficial technical effects: 1. This application utilizes a core-shell structure modified acrylic emulsion with an organosilicon / acrylate copolymer as the core and a fluorinated / acrylate copolymer as the shell. This enriches the fluorinated hydrophobic segments on the coating surface and concentrates the organosilicon elastic segments inside the coating, thereby achieving functional zoning of the interface within the coating. This achieves long-lasting anti-mildew and moisture-proof performance without adding traditional harmful anti-mildew agents, while also giving the coating film excellent elastic crack resistance, significantly improving the environmental friendliness and durability of the coating.

[0034] 2. This application uses fumed silica modified with KH-570 silane coupling agent to combine with glass fiber, so that the nanoporous silica and the three-dimensional fiber skeleton form a multi-layer acoustic structure of "absorption-reflection-absorption". At the same time, the double bonds introduced on the surface of the nanoparticles can chemically graft with the emulsion, which significantly improves the dispersibility of the filler and the interfacial bonding strength, thereby achieving high-efficiency sound insulation and sound absorption performance with a thin coating thickness of 3-5mm. Detailed Implementation

[0035] The present application will be further described in detail below with reference to embodiments and comparative examples: Some of the raw materials used in the examples and comparative examples: SDS (sodium dodecyl sulfate) and OP-10 (octylphenol polyoxyethylene ether) are both emulsifiers; fumed silica is hydrophobic and has a specific surface area of ​​200 m². 2 / g; KH-570 (i.e., 3-(isobutenoyloxy)propyltrimethoxysilane), CAS: 2530-85-0, both are from Shanghai Maclean Biochemical Technology Co., Ltd.

[0036] Titanium dioxide, crystal form: rutile titanium dioxide, item number: 05, purchased from Shanghai Jinghong Chemical Technology Co., Ltd.; Talc powder, product specification: 5000 mesh, item number: SD0258, purchased from Jiangsu Yuntong New Material Technology Co., Ltd.; Glass fiber, mesh number: 300 mesh, average fiber length: 50μm, fiber diameter: 9μm, model: NFFT9300, purchased from Shenzhen Xinxian Technology Co., Ltd.

[0037] In this application, the dispersant used is Dow Orotan™ 731A, the wetting agent used is Evonik Tego® Wet 270, the defoamer used is BYK-024, the film-forming aid used is Dow DOWANOL™ DPnB, the preservative used is Lanxess Proxel™ GXL, the pH adjuster used is Dow AMP-95™, and the thickener used is Dow Acrysol™ ASE-60. All of these have environmentally friendly characteristics such as low VOC, no APEO, and no formaldehyde.

[0038] Unless otherwise specified, all raw materials used in the examples and comparative examples are commercially available products.

[0039] Preparation Example 1 The modified acrylic emulsion was prepared as follows: S1. Mix 180 parts by weight of water, 2.5 parts by weight of emulsifier (prepared by mixing SDS and OP-10 in a weight ratio of 4:1), and 0.5 parts by weight of sodium bicarbonate, and stir to raise the temperature to 80°C. While stirring, add 100 parts by weight of a core layer monomer mixture (containing n-butyl acrylate, methyl methacrylate, and vinyltrimethoxysilane, wherein the weight ratio of n-butyl acrylate, methyl methacrylate, and vinyltrimethoxysilane is 9:7:4) dropwise over 30 minutes. After the addition is complete, continue stirring for pre-emulsification for 20 minutes. Then, add an ammonium persulfate initiator solution (prepared by dissolving 0.8 parts by weight of ammonium persulfate in 10 parts by weight of water), and maintain the temperature for 45 minutes to form a core layer seed emulsion. S2. 80 parts by weight of water, 1.5 parts by weight of emulsifier (prepared by mixing SDS and OP-10 in a weight ratio of 4:1) and 100 parts by weight of shell monomer mixture (containing n-butyl acrylate, dodecyl fluoroheptyl methacrylate and glycidyl methacrylate, wherein the weight ratio of n-butyl acrylate, dodecyl fluoroheptyl methacrylate and glycidyl methacrylate is 3:5:2) are stirred at 1000 rpm at room temperature for 45 minutes to form a shell pre-emulsion. S3. The shell pre-emulsion obtained in step S2 is added dropwise to the core seed emulsion obtained in step S1 over 3 hours, with the reaction temperature controlled at 80°C. During the addition, ammonium persulfate initiator solution is added in three separate additions (each addition of ammonium persulfate initiator solution is prepared by dissolving 0.2 parts by weight of ammonium persulfate in 5 parts by weight of water). After the addition is complete, the mixture is kept at this temperature for 1.5 hours, then cooled to 40°C, and the pH is adjusted to 7.5 with ammonia. The mixture is then filtered through a 200-mesh filter to obtain the modified acrylate emulsion.

[0040] Preparation Example 2 The difference between Preparation Example 2 and Preparation Example 1 is that the modified acrylate elastic emulsion is a silicone-modified acrylate elastic emulsion, that is, the dodecafluoroheptyl methacrylate in preparation step S2 is replaced with an equal amount of methyl methacrylate. The preparation steps are as follows: S1. Mix 180 parts by weight of water, 2.5 parts by weight of emulsifier (prepared by mixing SDS and OP-10 in a weight ratio of 4:1), and 0.5 parts by weight of sodium bicarbonate, and stir to raise the temperature to 80°C. While stirring, add 100 parts by weight of a core layer monomer mixture (containing n-butyl acrylate, methyl methacrylate, and vinyltrimethoxysilane, wherein the weight ratio of n-butyl acrylate, methyl methacrylate, and vinyltrimethoxysilane is 9:7:4) dropwise over 30 minutes. After the addition is complete, continue stirring for pre-emulsification for 20 minutes. Then, add an ammonium persulfate initiator solution (prepared by dissolving 0.8 parts by weight of ammonium persulfate in 10 parts by weight of water), and maintain the temperature for 45 minutes to form a core layer seed emulsion. S2. 80 parts by weight of water, 1.5 parts by weight of emulsifier (prepared by mixing SDS and OP-10 in a weight ratio of 4:1) and 100 parts by weight of shell monomer mixture (containing n-butyl acrylate, methyl methacrylate and glycidyl methacrylate, wherein the weight ratio of n-butyl acrylate, methyl methacrylate and glycidyl methacrylate is 3:5:2) are stirred at 1000 rpm at room temperature for 45 minutes to form a shell pre-emulsion. S3. The shell pre-emulsion obtained in step S2 is added dropwise to the core seed emulsion obtained in step S1 over 3 hours, with the reaction temperature controlled at 80°C. During the addition, ammonium persulfate initiator solution is added in three separate additions (each addition of ammonium persulfate initiator solution is prepared by dissolving 0.2 parts by weight of ammonium persulfate in 5 parts by weight of water). After the addition is complete, the mixture is kept at this temperature for 1.5 hours, then cooled to 40°C, and the pH is adjusted to 7.5 with ammonia. The mixture is then filtered through a 200-mesh filter to obtain the organosilicon-modified acrylate emulsion.

[0041] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that the modified acrylate elastic emulsion is a fluorinated modified acrylate elastic emulsion, that is, the vinyltrimethoxysilane in preparation step S1 is replaced by an equal amount of n-butyl acrylate. The preparation steps are as follows: S1. Mix 180 parts by weight of water, 2.5 parts by weight of emulsifier (prepared by mixing SDS and OP-10 in a weight ratio of 4:1), and 0.5 parts by weight of sodium bicarbonate, and stir to raise the temperature to 80°C. While stirring, add 100 parts by weight of a core layer monomer mixture (containing n-butyl acrylate and methyl methacrylate, wherein the weight ratio of n-butyl acrylate to methyl methacrylate is 13:7) dropwise over 30 minutes. After the addition is complete, continue stirring for pre-emulsification for 20 minutes. Then, add an ammonium persulfate initiator solution (prepared by dissolving 0.8 parts by weight of ammonium persulfate in 10 parts by weight of water), and maintain the temperature for 45 minutes to form a core layer seed emulsion. S2. 80 parts by weight of water, 1.5 parts by weight of emulsifier (prepared by mixing SDS and OP-10 in a weight ratio of 4:1) and 100 parts by weight of shell monomer mixture (containing n-butyl acrylate, dodecyl fluoroheptyl methacrylate and glycidyl methacrylate, wherein the weight ratio of n-butyl acrylate, dodecyl fluoroheptyl methacrylate and glycidyl methacrylate is 3:5:2) are stirred at 1000 rpm at room temperature for 45 minutes to form a shell pre-emulsion. S3. The shell pre-emulsion obtained in step S2 is added dropwise to the core seed emulsion obtained in step S1 over 3 hours, with the reaction temperature controlled at 80°C. During the addition, ammonium persulfate initiator solution is added in three separate additions (each addition of ammonium persulfate initiator solution is prepared by dissolving 0.2 parts by weight of ammonium persulfate in 5 parts by weight of water). After the addition is complete, the mixture is kept at this temperature for 1.5 hours, then cooled to 40°C, and the pH is adjusted to 7.5 with ammonia. The mixture is then filtered through a 200-mesh filter to obtain the fluorinated modified acrylate emulsion.

[0042] Preparation Example 4 The only difference between Preparation Example 4 and Preparation Example 1 is that in step S1 of Preparation Example 4, 100 parts by weight of the core layer monomer mixture is replaced with 40 parts by weight of the core layer monomer mixture; and in step S2, 100 parts by weight of the shell layer monomer mixture is replaced with 160 parts by weight of the shell layer monomer mixture.

[0043] Preparation Example 5 The only difference between Preparation Example 5 and Preparation Example 1 is that in step S1 of Preparation Example 5, 100 parts by weight of the core layer monomer mixture is replaced with 160 parts by weight of the core layer monomer mixture; and in step S2, 100 parts by weight of the shell layer monomer mixture is replaced with 40 parts by weight of the shell layer monomer mixture.

[0044] Preparation Example 6 The preparation of KH-570 modified fumed silica is as follows: Mix 500 parts by weight of ethanol and 50 parts by weight of water, and stir until homogeneous to form an alcohol-water mixed solvent. Adjust the pH to 4.0 with glacial acetic acid. Slowly add 100 parts by weight of fumed silica while stirring, and disperse at 1000 rpm for 30 minutes at room temperature to form a homogeneous suspension. Dissolve 10 parts by weight of KH-570 in 20 parts by weight of a 70% ethanol aqueous solution, stir until homogeneous, and hydrolyze at room temperature for 15 minutes to obtain a hydrolysate of KH-570. Add the hydrolysate of KH-570 to the suspension, and reflux at 80°C for 5 hours. After the reaction is complete, centrifuge to separate the solids. Wash the solids three times with ethanol, dry them under vacuum at 80°C for 5 hours, and grind them through a 300-mesh sieve to obtain KH-570 modified fumed silica. Example Example 1

[0045] 0.5 parts by weight of dispersant, 0.1 parts by weight of wetting agent, 0.3 parts by weight of defoamer, 2.5 parts by weight of film-forming aid, 0.3 parts by weight of preservative, and 0.1 parts by weight of pH adjuster were dispersed in 10 parts by weight of water and stirred evenly. Then, while stirring at 800 rpm, 20 parts by weight of titanium dioxide, 5 parts by weight of talc, 3 parts by weight of KH-570 modified fumed silica prepared in Preparation Example 6, and 11 parts by weight of glass fiber were added sequentially. After the addition was complete, the stirring speed was increased to 1200 rpm and the mixture was dispersed for 30 minutes. Then, the stirring speed was reduced to 600 rpm, and 50 parts by weight of modified acrylic emulsion prepared in Preparation Example 1 were added and stirred evenly. Finally, 0.3 parts by weight of thickener (pre-diluted with an equal mass of water) was slowly added to adjust the coating viscosity to 100 KU. The mixture was then filtered through a 200-mesh filter to obtain a water-based, mildew-proof, moisture-proof, sound-insulating, sound-absorbing, environmentally friendly, and elastic wall coating. Example 2

[0046] The only difference between Example 2 and Example 1 is that in the preparation of Example 2, 50 parts by weight of the modified acrylate emulsion prepared in Preparation Example 1 were replaced with 50 parts by weight of the modified acrylate emulsion prepared in Preparation Example 4. Example 3

[0047] The only difference between Example 3 and Example 1 is that in the preparation of Example 3, 50 parts by weight of the modified acrylate emulsion prepared in Preparation Example 1 were replaced with 50 parts by weight of the modified acrylate emulsion prepared in Preparation Example 5. Example 4

[0048] The only difference between Example 4 and Example 1 is that in the preparation of Example 4, 3 parts by weight of the KH-570 modified fumed silica prepared in Example 6 were replaced with 3 parts by weight of fumed silica. Example 5

[0049] The only difference between Example 5 and Example 1 is that in the preparation of Example 5, 20 parts by weight of titanium dioxide and 5 parts by weight of talc are replaced with 25 parts by weight of titanium dioxide. Example 6

[0050] The only difference between Example 6 and Example 1 is that in the preparation of Example 6, 20 parts by weight of titanium dioxide and 5 parts by weight of talc are replaced with 25 parts by weight of talc. Example 7

[0051] The only difference between Example 7 and Example 1 is that in the preparation of Example 7, 20 parts by weight of titanium dioxide and 5 parts by weight of talc are replaced with 26 parts by weight of titanium dioxide and 4 parts by weight of talc. Example 8

[0052] The only difference between Example 8 and Example 1 is that in the preparation of Example 8, 20 parts by weight of titanium dioxide and 5 parts by weight of talc are replaced with 12.5 parts by weight of titanium dioxide and 12.5 parts by weight of talc.

[0053] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that, in the preparation of Comparative Example 1, 50 parts by weight of the modified acrylate emulsion prepared in Preparation Example 1 were replaced with 50 parts by weight of the organosilicon modified acrylate emulsion prepared in Preparation Example 2.

[0054] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that, in the preparation of Comparative Example 2, 50 parts by weight of the modified acrylate emulsion prepared in Preparation Example 1 were replaced with 50 parts by weight of the fluorinated modified acrylate emulsion prepared in Preparation Example 3.

[0055] The elastic wall coatings prepared in each embodiment and comparative example were subjected to performance tests for VOC content, mildew resistance, sound absorption coefficient, and mechanical strength according to the following standards: 1. The VOC content was tested according to GB 18582-2020 "Limits of Hazardous Substances in Wall Coatings for Buildings". Each sample was tested 3 times and the average value was taken. 2. According to the ASTM G21-15 standard and method for determining the antifungal properties of synthetic polymer materials, elastic wall coating was applied to a 2cm*2cm metal sheet and cured to form a coating, thus preparing a test sample. This sample was placed in a suspension containing *Chaetoceros globosum* ATCC 6205, *Aspergillus niger* ATCC 9642, *Trichoderma viride* CICC 2535, *Penicillium cordifolium* ATCC 11797, and *Brachystomata buddingii* ATCC 15233, with a spore suspension concentration of 2.7 × 10⁻⁶. 6 The samples were cultured for 28 days at a test temperature of 28℃±2 and a relative humidity of 85%±5. The area of ​​mold growth (after 28 days) and the mold resistance level (after 28 days) were measured. The fungal growth observed on the surface of the samples was measured, and the performance was evaluated according to the following standards. 0 - No growth, 1 - Trace growth (less than 10%), 2 - Slight growth (10-30%), 3 - Moderate growth (30-60%), 4 - Severe growth (60% - complete coverage); In accordance with GB / T 18696.2-2002 "Measurement of sound absorption coefficient and acoustic impedance in acoustic impedance tubes - Part 2: Transfer function method", report the NRC (noise reduction coefficient) in the frequency range of 200-2000 Hz. Referring to GB / T 16777-2008 "Test Methods for Waterproof Coatings for Buildings", the elongation at break (%) and tensile strength (MPa) were tested at a tensile speed of 200 mm / min.

[0056] All the test results are summarized in Table 1 below. Table 1. Performance data of elastic wall coatings prepared in each embodiment and comparative example.

[0057] As can be seen from Examples 1-8 and Table 1, the core-shell ratio control, KH-570 modification, and pigment and filler blending are all indispensable and jointly determine the overall performance of the coating. In Example 1, the core-shell weight ratio was controlled at 1:1. The fluorinated segments in the shell layer enriched the surface, providing excellent hydrophobic and mildew-resistant properties, while the silicone segments in the core layer provided high elasticity. Simultaneously, the KH-570-modified fumed silica and glass fiber formed a stable "absorption-reflection-absorption" multilayer acoustic structure. The 4:1 blend of titanium dioxide and talc further improved the coating's density and mechanical balance. In contrast, Example 2 suffered from a brittle coating due to insufficient core layer; Example 3 experienced decreased mildew resistance and insufficient strength due to insufficient shell layer; Example 4 showed a significant reduction in sound insulation due to the absence of KH-570-modified fumed silica; Examples 5-6 exhibited decreased coating density due to the use of a single filler; and Examples 7-8, due to deviations in the pigment and filler ratio from the optimal range, had slightly lower overall performance than Example 1 but were still superior to the single filler system. The above fully demonstrates that Example 1, through the synergistic optimization of various components and process parameters, achieves the best comprehensive performance of being highly environmentally friendly, having a long-lasting anti-mildew effect, providing efficient sound insulation, and being both "soft and strong".

[0058] Combining Example 1 and Comparative Examples 1-2, and referring to Table 1, it can be seen that the simultaneous presence of an organosilicon core and a fluorinated shell in the core-shell structure is a necessary condition for achieving the synergistic effect of high elasticity and long-lasting mildew resistance. Comparative Example 1, lacking a fluorinated shell layer, although having a similar elongation at break to Example 1, exhibited significantly deteriorated mildew resistance, a substantial reduction in sound insulation, and insufficient tensile strength. Comparative Example 2, lacking an organosilicon core, while having the same tensile strength and mildew resistance as Example 1, had extremely low elongation at break, resulting in a brittle and easily cracked coating, completely losing the crack resistance advantage of elastic coatings. This fully demonstrates that only when both an organosilicon core and a fluorinated shell are present in the core-shell structure can high elasticity, high strength, efficient sound insulation, and long-lasting mildew resistance be achieved simultaneously. The absence of either component leads to a significant deterioration of a key performance characteristic, failing to meet the comprehensive performance requirements of wall coatings.

[0059] This application achieves a stable multi-layered composite network after the coating is cured by using a core-shell structure modified acrylic emulsion interface functional zoning design, KH-570 surface grafted modified fumed silica to achieve chemical bonding between inorganic fillers and organic matrix, a multi-layered "absorption-reflection-absorption" acoustic structure constructed by glass fiber and modified silica, and optimized compounding of titanium dioxide and talc. This unexpectedly achieves high environmental protection, long-lasting mildew prevention, high-efficiency sound insulation and "both soft and strong" comprehensive performance at a thin coating thickness, overcoming the technical problem of existing wall coatings having single function and sacrificing some aspects.

[0060] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A water-based, mildew-proof, moisture-proof, sound-insulating, sound-absorbing, environmentally friendly, and elastic wall coating, characterized in that: The raw materials for preparation include the following components in parts by weight: 40-60 parts of modified acrylate emulsion, 20-30 parts of pigments and fillers, 1-10 parts of fumed silica, 5-15 parts of glass fiber, 1-10 parts of additives, 1-10 parts of water, and 0.1-1% of thickener; the modified acrylate emulsion is a core-shell structured emulsion with an organosilicon monomer / acrylate copolymer as the core and a fluorinated monomer / acrylate copolymer as the shell.

2. The water-based anti-mildew, moisture-proof, sound-insulating, sound-absorbing, environmentally friendly, and elastic wall coating according to claim 1, characterized in that, The preparation of the modified acrylate emulsion includes the following steps: S1. After mixing water, emulsifier, and sodium bicarbonate, add a mixture of core layer monomers (including n-butyl acrylate, methyl methacrylate, and organosilicon monomers) dropwise. After stirring and pre-emulsifying, add ammonium persulfate initiator solution dropwise to react and form a core layer seed emulsion. S2. Mix water, emulsifier and shell monomer mixture (including n-butyl acrylate, dodecafluoroheptyl methacrylate and functional monomers) to form shell pre-emulsion; S3. The shell pre-emulsion obtained in step S2 is added dropwise to the core seed emulsion obtained in step S1 to carry out a core-shell polymerization reaction. Ammonium persulfate initiator solution is added to carry out a ripening reaction. The modified acrylate emulsion is then obtained through post-treatment.

3. The water-based anti-mildew, moisture-proof, sound-insulating, sound-absorbing, highly environmentally friendly, and elastic wall coating according to claim 2, characterized in that, The functional monomer mentioned in step S2 is selected from one or two of glycidyl methacrylate and hydroxyethyl acrylate.

4. The water-based anti-mildew, moisture-proof, sound-insulating, sound-absorbing, highly environmentally friendly, and elastic wall coating according to claim 2, characterized in that, In the preparation of the modified acrylate emulsion, the weight ratio of the core monomer mixture to the shell monomer mixture is (0.8-1.2):

1.

5. The water-based anti-mildew, moisture-proof, sound-insulating, sound-absorbing, highly environmentally friendly, and elastic wall coating according to claim 1, characterized in that, The fumed silica is modified with a silane coupling agent.

6. The water-based anti-mildew, moisture-proof, sound-insulating, sound-absorbing, environmentally friendly, and elastic wall coating according to claim 5, characterized in that, The silane coupling agent is KH-570.

7. The water-based anti-mildew, moisture-proof, sound-insulating, sound-absorbing, environmentally friendly, and elastic wall coating according to claim 1, characterized in that, The pigments and fillers are selected from one or two of titanium dioxide and talc.

8. The water-based anti-mildew, moisture-proof, sound-insulating, sound-absorbing, environmentally friendly, and elastic wall coating according to claim 7, characterized in that, The pigments and fillers include titanium dioxide and talc, and the weight ratio of titanium dioxide to talc is (2-5):

1.

9. The water-based anti-mildew, moisture-proof, sound-insulating, sound-absorbing, environmentally friendly, and elastic wall coating according to claim 1, characterized in that, The additives include dispersants, wetting agents, defoamers, film-forming aids, preservatives, and pH adjusters.

10. A method for preparing a water-based anti-mildew, moisture-proof, sound-insulating, sound-absorbing, highly environmentally friendly, and elastic wall coating according to any one of claims 1-9, characterized in that, Includes the following steps: The additives are dispersed in water and stirred evenly. Under stirring conditions, pigments, fillers, fumed silica, and glass fiber are added in sequence, followed by modified acrylic emulsion. The mixture is stirred evenly, and finally, a thickener is added to adjust the viscosity of the coating to 80-120 KU. The coating is then filtered to obtain the water-based anti-mildew, moisture-proof, sound-insulating, sound-absorbing, environmentally friendly, and elastic wall coating.